Luminous Diamond

By subjecting precursor diamond grains to high pressure/high temperature conditions to create nitrogen vacancy defects and then resizing them, the production of luminescent nanodiamonds becomes more efficient and cost-effective, achieving significantly higher emission intensities.

JP7669273B2Active Publication Date: 2025-04-28SCHLUMBERGER TECHNOLOGY BV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021541278
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-01-16
Filing Date
2020-01-15
Publication Date
2025-04-28
Estimated Expiration
2040-01-15

AI Technical Summary

Technical Problem

Current methods for producing luminescent nanodiamonds are expensive, energy and time-consuming, limiting their availability and increasing their cost.

Method used

Subjecting precursor diamond grains to high pressure/high temperature conditions to induce plastic deformation, creating nitrogen vacancy defects and enhancing light emission activity, followed by resizing to increase surface area and luminescent intensity.

Benefits of technology

The resulting luminescent diamonds exhibit emission intensities at least two orders of magnitude higher than precursor diamond grains, with improved manufacturing efficiency and expanded potential end uses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669273000002
    Figure 0007669273000002
  • Figure 0007669273000003
    Figure 0007669273000003
  • Figure 0007669273000004
    Figure 0007669273000004
Patent Text Reader

Abstract

Luminescent diamonds are produced by subjecting a quantity of diamond grains to high pressure / high temperature conditions, with or without a catalyst, to plastically deform the grains and generate nitrogen vacancy defects in the diamond grains, resulting in diamond material with enhanced luminescence activity / intensity. The solidified diamond material may be further processed to further enhance its luminescence activity / intensity, which may include grinding the solidified diamond material into diamond particles, heat treatment in a vacuum, and hot air treatment, with the grinding process further enhancing its luminescence activity / intensity. The resulting luminescent diamond particles exhibit a higher level of luminescence intensity than that of conventional luminescent nanodiamonds and may be functionalized for use in biological applications.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This patent application claims priority to and the benefit of U.S. Provisional Patent Application No. 62 / 793,032, entitled "Luminescent Diamond," filed January 16, 2019, which is hereby incorporated by reference in its entirety. [Background technology]

[0002] Laser-induced fluorescence is a known technique employed to better understand how biological systems function at the molecular level by probing individual biomolecules for observation. In one example, laser-induced fluorescence may be applied to image and track single molecules or particles in living cells or the like, such as in vivo biological sensors for organ mapping, cell imaging, and the like. One type of material used for laser-induced fluorescence is luminescent nanodiamonds, which are nano-sized diamond particles or grains that have been developed to emit light when excited by a light source within the desired wavelength range required for the end application. Although the existence of luminescent nanodiamonds is known, the methods and techniques currently used to make such luminescent nanodiamonds are expensive, energy- and time-intensive, which not only adds to the cost of the material but also limits its availability for the desired application. Summary of the Invention

[0003] Luminescent diamond and methods of making the same are disclosed herein, which include subjecting a quantity of precursor diamond grains to high pressure / high temperature conditions to plastically deform the grains and generate nitrogen vacancy defects in the diamond grains, thereby increasing the activity and intensity of the luminescence of the resulting diamond material relative to that of the precursor diamond grains. In some embodiments, the solidified diamond material may have an luminescence intensity at least about two orders of magnitude higher than that of the precursor diamond powder. In some embodiments, the quantity of diamond grains may or may not include a catalyst material, in which case the solidified diamond material may be a body of mechanically bonded or semi-sintered diamond grains or a fully sintered polycrystalline body. In some embodiments where a polycrystalline body is produced, the amount of catalyst material used may be less than the amount useful for producing a fully sintered polycrystalline body. In some embodiments, the catalyst material may be a metal solvent catalyst or a carbonate catalyst, and the use of a carbonate catalyst produces a carbonate PCD body with a different level of luminescence intensity than that of a cobalt PCD body. This difference may be manifested in the spectral position and / or intensity of the resulting emission peak.

[0004] The diamond material formed by the high pressure / high temperature process may be treated to further increase the level of the luminescence intensity of the diamond material. In some embodiments, such treatment may be separate from and prior to the grinding of the diamond material into diamond particles. The diamond material formed by the high pressure / high temperature process is subjected to a grinding or resizing process to form diamond particles having a desired particle size. In some embodiments, the diamond material may be resized to have nanometer-sized diamond particles. During size reduction, the diamond material has an increased surface area exposed to the radiation source that produces the luminescence, thereby increasing the resulting strength, and may also undergo further plastic deformation, which may result in an even higher luminescence intensity compared to the solidified diamond material. In some embodiments, the resized diamond particles have a luminescence intensity that is at least about 10 percent higher than that of the diamond material formed during the high pressure / high temperature process. In some embodiments, another method to increase the luminescence activity is to repeat the HPHT process on a previously HPHT-treated diamond material, such as heat treatment in air or an inert atmosphere, heat treatment in an oxygen atmosphere, or a combination with a controlled oxygen partial pressure. The resized and heat treated luminescent diamond particles can be functionalized to tailor them to a desired end use. The luminescent diamonds described herein exhibit comparable or higher levels of luminescence intensity compared to conventional luminescent diamonds and are made in a more efficient manner compared to such conventional luminescent diamonds.

[0005] This Summary is provided to introduce selected concepts that are further described below in the Detailed Description. This Summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used as an aid in limiting the scope of the claimed subject matter.

[0006] These and other features and advantages of the luminescent nanodiamonds and methods of making the same disclosed herein will be appreciated as the same becomes better understood by reference to the following detailed description, when considered in conjunction with the accompanying drawings. [Brief description of the drawings]

[0007] [Figure 1] 1 is a graph showing emission intensity and wavelength information for diamond powders disclosed herein when subjected to various elevated temperatures. [Figure 2A] FIG. 2 is a graph showing emission intensity and wavelength information at various grain sizes for polycrystalline diamond material with a cobalt catalyst as disclosed herein; [Figure 2B] FIG. 2 is a graph showing emission intensity and wavelength information at various grain sizes of polycrystalline diamond material comprising a carbonate catalyst as disclosed herein; [Diagram 3] FIG. 2 is a graph showing the emission intensity and wavelength information of polycrystalline diamond material comprising a carbonate catalyst as disclosed herein with and without vacuum heat treatment. [Figure 4] FIG. 1 is a graph showing the emission intensity and wavelength information of polycrystalline diamond material with a carbonate catalyst that has been sized to diamond particles and subjected to air heat treatment at various temperatures. [Diagram 5] FIG. 1 is a block diagram showing the processing steps for making luminescent diamond as described herein. [Figure 6] 2 is a graph showing the luminescence intensity and wavelength information of the luminescent diamond material disclosed herein in comparison with conventional luminescent diamond; [Figure 7] FIG. 2 is a graph showing the relative luminescence intensity of the luminescent diamond material disclosed herein in the sintered state compared to conventional luminescent nanodiamond. [Figure 8] 1 is a graph showing the relative luminescence intensity of the luminescent diamond material disclosed herein in the sintered state as a function of processing pressure and in relation to diamond powder that has not been subjected to a high pressure / high temperature process. [Figure 9]FIG. 2 is a graph showing the relative luminescence intensity of the luminescent diamond material disclosed herein in its crushed state compared to conventional luminescent nanodiamonds. [Figure 10] FIG. 2 is a bar graph showing the relative luminescence intensity of the luminescent diamond material disclosed herein in both sintered and crushed states compared to conventional luminescent nanodiamonds. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] In some embodiments, the luminescent diamonds (e.g., photoluminescent diamonds) and methods of making them disclosed herein are manipulated in a manner that increases production efficiency and yield, thereby improving the availability and accessibility of the material for end uses, including but not limited to the biological uses briefly mentioned above. Furthermore, in some embodiments, luminescent diamonds prepared according to the principles disclosed herein exhibit similar or higher levels of luminescence intensity compared to conventional luminescent diamonds, thereby providing an opportunity to expand the range of potential end uses of such materials. For clarity, in some embodiments, the luminescent diamonds disclosed herein are formed by first solidifying and consolidating existing diamond grains to form a sintered or mechanically bonded semi-sintered luminescence active body or nodule. The solidified material in such conditions is referred to herein as luminescent diamond. During a subsequent step, the luminescent diamond is reduced to the size required for the particular end use, and in some embodiments, the resulting diamond grains or grains are nanoscale in size. In some cases, the size-reduced luminescent diamonds may be only nano-sized grains or may include an admixture of nano-sized grains and coarse diamond grains. The term "nanodiamond" as used herein is understood to refer to luminescent diamond including nano-sized diamond particles, i.e. having an average particle size of about 1-1000 nm.

[0009] In some embodiments, the luminescent diamond disclosed herein may be formed by mixing a quantity of precursor diamond grains, which may be in the form of natural and / or synthetic diamond grains, and placing the quantity of diamond grains in a can or container conventionally used for solidifying diamond grains. In one example, the diamond grains may have an average grain size of about 1-1000 μm, about 1-100 μm, and about 10-50 μm. In other embodiments, the size of the starting diamond grains or powder may range from submicron or nanodiamond above. In some embodiments, nano-sized powders formed by either mechanical crushing or detonation processes of conventional diamond powders may be used in a similar manner. Conventional diamond powders may be either synthetic or natural, but synthetic diamond powders generally have a higher intrinsic nitrogen content, which together with nearby vacancies makes the diamond luminescently active. In one example, the starting diamond material should have an intrinsic amount of nitrogen impurity consistent with that found in diamonds designated as type 1b, specifically about 50 ppm or more of nitrogen. Nanopowders synthesized by impact synthesis also generally have a higher intrinsic nitrogen content. In some embodiments, the container and its contents are subjected to a high pressure / high temperature (HPHT) solidification process using conventional pressing equipment for making polycrystalline diamond. In some embodiments, a quantity of diamond grains is placed in a can or container, which may or may not be sealed, and placed in an HPHT press and subjected to the desired sintering pressure and temperature conditions. In some embodiments, the HPHT process temperature may range from about 1300 to 2200°C, and the process pressure may range from about 5.0 GPa to about 10 GPa. In some embodiments, the quantity of diamond grains is substantially free of any catalytic material, such that the diamond material resulting from the HPHT process is in the form of a semi-sintered nodule or body that includes diamond grains that are mechanically bonded together by frictional contact, low temperature welding, diamond self-diffusion, etc., rather than being fully sintered.A feature of using conventional metal solvent catalysis to produce diamond material that is not fully sintered, i.e. not semi-sintered and characterized by a network of interlocking diamond grains, is that its relative transparency may be improved compared to sintered polycrystalline diamond bodies, which may enhance the intensity of the luminescence emission therefrom. There may also be graphite that forms in the porous areas of the semi-sintered body, which may reduce the intensity of the luminescence. In such cases, it may be desirable to partially or completely remove the graphite material as part of the manufacturing process.

[0010] It has been discovered that during the HPHT process, at least a portion of the precursor diamond grain mass undergoes plastic deformation. In some embodiments, the extent of the HPHT solidification process is such that it induces sufficient plastic deformation in the diamond grain to create nitrogen vacancy (NV, or NVN) defects in the diamond grain that act to make the diamond grain luminescence active. The plastic deformation of diamond particles during HPHT is believed to create vacancies as deformation mechanisms, such as crystallographic dislocation motion, become more active, which in turn combine with nitrogen impurities to form nitrogen vacancy (NV, or NVN) defects that create the desired luminescence activity. In some embodiments, this occurs during conventional sintering of polycrystalline diamond with a metal or nonmetal catalyst, such as cobalt and magnesium carbonate, respectively. In other embodiments, the diamond grains obtained from the HPHT process may be highly plastically deformed with many NV or NVN defects and weak diamond-diamond bonds compared to solvent-catalyzed polycrystalline diamond. For example, in some embodiments it is desirable for the diamond grains during the HPHT process to undergo such plastic deformation that produces luminescence activity without becoming a fully sintered body, thereby making downstream processes of resizing the diamond grains, such as crushing processes, simpler and less energy intensive, requiring only mechanical disruption of bonded diamond grains.

[0011] In some embodiments, the luminescent diamonds disclosed herein may be formed in a similar manner by subjecting a quantity of diamond precursor grains to a HPHT process in the presence of a catalytic material. In such embodiments, the type of catalytic material used may be selected from the group including, but not limited to, Co, Fe, Ni, carbonate, Si, and combinations thereof to form polycrystalline diamond (PCD). In some embodiments, the HPHT processing conditions for cobalt PCD may be in the range of temperatures of about 1300-1500°C and pressures of about 5.0-7.5 GPa. In addition, cobalt PCD is typically heat treated in vacuum at temperatures of 600-700°C. The amount of catalytic material used may and is likely to vary depending on factors such as the type of catalyst used, the amount of luminescence desired, and the specific end use. In biological end uses, the presence of metallic materials in the luminescent diamond may be undesirable and / or unacceptable for biodegradability reasons, in which case it may be desirable to use a non-metallic catalyst. In some embodiments, the use of a non-metallic catalyst results in a PCD body having a relatively high transparency or reduced opacity when compared to PCD formed using a metallic solvent catalyst. In some embodiments, non-metal catalysts useful for making luminescent diamonds disclosed herein include carbonate catalysts, such as magnesium carbonate, calcium carbonate, etc., resulting in the formation of carbonate PCD (CPCD). In an exemplary embodiment, the amount of such carbonate catalyst may be sufficient to form a fully sintered carbonate PCD body, such as about 5 weight percent or less based on the total weight of the carbonate catalyst and diamond grains. Carbonate PCD appears to be inherently brighter / more transparent than cobalt PCD, which is believed to contribute to the higher level of luminescence emission and intensity. In some embodiments, the HPHT processing of carbonate PCD may be performed at temperatures of about 1700-3000°C and pressures of greater than about 7.0 GPa. Additionally, carbonate PCD may be heat treated to temperatures of about 500-1300°C in an inert or vacuum environment.Regarding the above embodiment, HPHT processing causes plastic deformation in diamond grains, which results in the creation of NV or NVN defects that lead to an increase in the level of luminescence activity / intensity compared to precursor diamond grains.Some vacancies formed during HPHT may not combine with nitrogen during plastic deformation process and may move to the neighboring sites of nitrogen during heat treatment, resulting in the creation of additional NV or NVN sites.The higher temperature and pressure conditions of processing for carbonate PCD may cause a higher degree of plastic deformation in diamond grains, thus resulting in higher luminescence activity.Using a higher heat treatment temperature may also contribute to additional NV or NVN defects and therefore higher luminescence activity.

[0012] In some embodiments, it may be desirable to use less catalyst material than would be useful to form a fully sintered PCD body, for example less than about 5 weight percent catalyst (relative to the total weight of the diamond layer or PCD body). In such embodiments, it may be desirable to produce a partially sintered or semi-sintered PCD body that includes both intercrystalline bonded diamond and free diamond grains for the purpose of simplifying downstream processes of resizing the PCD body into nano-sized diamond flakes or grains, as better described below. It has been discovered that PCD made by the methods disclosed herein produces a level of luminescence intensity higher than that of conventional luminescent nanodiamonds, and thus producing a product with some PCD during HPHT processing, even without producing a fully sintered diamond body, may produce a desired increase in luminescence intensity, while also making downstream processes of resizing relatively simpler and less energy intensive than those that necessarily involve a fully sintered PCD body. Thus, by adjusting the amount of catalyst material, a diamond material may be obtained with a desired degree of sintering that both produces a desired increase in luminescence intensity and at the same time simplifies downstream resizing processes.

[0013] 1 is a graph 100 of luminescence intensity versus wavelength showing the effect of HPHT temperature on diamond grains without catalytic material subjected to a hydraulic pressure of approximately 13.5 ksi (cell pressure of 7.3-7.7 GPa) and a series of various temperatures from 1500° C. to 2300° C. In particular, the graph shows the luminescence characteristics of diamond grains 102 subjected to a HPHT process at 1500° C., diamond grains 104 subjected to a HPHT process at 1750° C., diamond grains 106 subjected to a HPHT process at 2000° C., diamond grains 108 subjected to a HPHT process at 2175° C., and diamond grains 110 subjected to a HPHT process at 2300° C. The diamond grains subjected to each of the above HPHT processes had an average grain size of approximately 10 μm. It is well known that NV centers in diamond produce red emission with a peak centered at about 675 nm, and NVN centers in diamond produce green emission with a peak centered at about 525 nm. This test demonstrated that both NV and NVN emission can be produced in the same diamond material depending only on the HPHT temperature. The emission characteristics shown in Figure 1 were produced by subjecting an example diamond grain to 489 nm laser irradiation collected by a spectrometer. These tests showed that HPHT temperature conditions of 1750, 2000, 2175 and 2300 °C produced NVN emission of various intensities, while only the HPHT temperature condition of 1500 °C produced NV emission.

[0014] 2A and 2B are graphs 200 and 220 showing the effect of particle size on NV and NVN emission intensity from a 488 nm laser source. FIG. 2A shows the emission intensity from a conventional cobalt-catalyzed polycrystalline diamond (PCD) material for shear applications sintered at approximately 11 ksi (6.5-6.9 GPa) and 1450° C. and having a cobalt content of approximately 10 weight percent based on the total weight of the PCD material. The PCD material was formed from diamond grains having an average grain size of approximately 17 μm. The PCD material was tested in the form of pellets 202 having a size of approximately 1 mm, crushed PCD particles 204 having an average grain size of approximately 80 μm, and crushed PCD particles 206 having an average grain size of approximately 5 μm. The testing demonstrated that the PCD material exhibited an increase in emission intensity with a decrease in the PCD material grain size.

[0015] FIG. 2B shows the emission intensity from a magnesium polycrystalline diamond (CPCD) material sintered at 13.5 ksi (7.3-7.7 GPa) and 2200° C. with a magnesium carbonate content of approximately 8 weight percent based on the total weight of the CPCD material. The CPCD material was formed from diamond grains with an average grain size of approximately 2 μm. The CPCD material was tested in the same size forms as the PCD material described above. Specifically, the CPCD material was tested in the form of pellets 222 with a size of approximately 1 mm, crushed CPCD particles 224 with an average grain size of approximately 80 μm, and crushed CPCD particles 226 with an average grain size of approximately 5 μm. In both cases (FIGS. 2A and 2B), it was observed that the emission intensity of each PCD and CPCD material increased with decreasing grain size. In some embodiments, the increase in emission intensity may be primarily a result of a larger surface area exposed to the laser excitation source due to the reduced grain size. By comparing with the non-crushed pellet material, the intensity increase was shown to be approximately four times higher in both examples. It is predicted that further increases in luminescence intensity are possible by crushing into even finer particles.

[0016] FIG. 3 is a graph 300 showing the effect of heat treating CPCD material (described above with respect to FIG. 2B and having an average grain size of approximately 2 μm) at approximately 1100° C. under vacuum conditions on the emission intensity. The emission intensity of the CPCD sample that was not subjected to heat treatment is shown as 302, while the emission intensity of the CPCD sample that was subjected to the heat treatment is shown as 304. As shown, the emission intensity of the heat treated sample 304 is 2.2 times higher than the non-heat treated sample 302. In some embodiments, this increase in emission intensity may be the result of the formation of additional NVN centers due to diffusive nitrogen migration during the heat treatment process. The ability to achieve an increase in emission intensity at green wavelengths by heat treatment alone at a relatively low temperature, e.g., without the need for high HPHT pressure, was unexpected. FIG. 3 also shows the relative increase in emission intensity when compared to raw diamond powder 306 that was not subjected to the HPHT process disclosed herein.

[0017] FIG. 4 is a graph 400 showing the effect of heat treatment of a CPCD material under oxidative conditions. The baseline CPCD material was formed under HPHT conditions of approximately 13.5 ksi water pressure (cell pressure 7.3-7.7 GPa) and approximately 2200° C., and had a magnesium carbonate content of approximately 8 weight percent based on the total weight of the CPCD material. The CPCD material was formed from diamond grains having an average grain size of approximately 2 μm. The CPCD material was crushed to approximately 5 μm and heat treated at 1100° C. under vacuum conditions. The oxidative heat treatment was carried out in air at temperatures of approximately 650, 675, and 700° C. for the same exposure time of approximately 120 minutes. The graph 400 shows the emission intensity of sample 402 not subjected to oxidative heat treatment, sample 404 subjected to 650° C., sample 406 subjected to 675° C., and sample 408 subjected to 700° C. The emission intensity was shown to increase progressively with increasing treatment temperature such that an overall increase of about 10 times in emission intensity (compared to the untreated sample) was observed. The heat treatment was accompanied by a progressive whitening of the material, from a dark grey color to a near white state, which is believed to be due to a change in the surface chemistry towards oxygen-terminated bonds at the diamond surface.

[0018] FIG. 5 is a block diagram 500 showing a process that may be used to make luminescent diamond. In one example, the process may be performed in a sequence including two or more steps as shown. In a first process 502, materials useful for making luminescent diamond are mixed and aggregated in a manner as described above which may or may not include the use of a catalyst material, which includes subjecting the aggregated or mixed materials to a HPHT process which may or may not result in the formation of a fully sintered diamond compact. In some embodiments, the first process 502 creates vacancies in the resulting diamond material for the formation of nitrogen (NV and / or NVN) defects as described above. In a second optional process 504, the diamond material resulting from the first process 502 is subjected to a heat treatment process under vacuum conditions. As described above, with respect to the luminescence intensity results shown in FIG. 3, in some embodiments, subjecting the diamond material after the first step 502 to such a heat treatment further increases the luminescence intensity of the diamond material (e.g., 1.5 to 2.2 times that of non-heat treated diamond material) by increasing the number of nitrogen defects (i.e., NVN). In a third optional process 506, the diamond material from the first process 502 or the second process 504 is reduced in size by crushing or other sizing techniques as described above. The exact size of the diamond particles formed during this third step may depend on the specific end use of the luminescent diamond material. Various diamond particle sizes for the luminescent diamond material are disclosed above. During this third process 506, the diamond material is converted to a powder. In some embodiments, reducing the size of the diamond material results in a 3-4 times higher luminescence intensity of the diamond material due to an increase in the surface area of ​​the resulting powder. In a fourth optional process 508, the diamond material from the first process 502, the second process 504 or the third process 506 is subjected to an air heat treatment, e.g., an oxidative heat treatment as described above with respect to the luminescence intensity results shown in FIG. 4). In some embodiments, the air heat treatment whitens the surface of the diamond material, which is believed to be due to the formation of oxygen-terminated diamond bonds.As noted above, with respect to the luminescence intensity results shown in Figure 4, in some embodiments, subjecting the diamond material to this fourth process 508 results in approximately a ten-fold increase in luminescence intensity. As noted above, in some embodiments, the luminescent diamond material disclosed herein may be formed according to one or more of these processes, and in some embodiments may be formed using all of these processes in sequence, depending on the degree of luminescence intensity required for a particular end use application.

[0019] FIG. 6 is a graph showing the luminescence intensity of luminescent diamond material made using all the processes shown in FIG. 5. The diamond material was a CPCD formed by HPHT process at 13.5 ksi and 2,200° C., which contained about 8 weight percent magnesium carbonate based on the total weight of the CPCD. The CPCD material was formed from diamond grains having an average grain size of about 2 μm. The resulting CPCD was subjected to vacuum heat treatment at a temperature of about 1100° C. for a period of about 60 minutes (second step). The resulting heat-treated CPCD was sized or crushed to an average diamond grain size of about 5 μm with removal of coarser grains by a -170 mesh sieve. The resulting diamond grains were then subjected to air heat treatment at a temperature of about 700° C. for 120 minutes. The luminescence intensity of the resulting material is shown on the graph as 602 and compared to that of a commercially available luminescent nanodiamond material with an average grain size of about 1 μm, shown on the graph as 604. From the graph 600, it can be seen that the luminescence results of the luminescent diamond disclosed herein are comparable (within 15%) to commercially available luminescent nanodiamond materials.The luminescent diamond material disclosed herein was tested with an average grain size of 5 μm, which is 5 times larger than the average grain size of commercially available luminescent nanodiamond materials, so it is expected that the equivalent or better NVN intensity can be achieved by further reducing the grain size.Further optimization / modification of the heat treatment process is also expected to further increase the luminescence intensity.

[0020] Figure 7 is a graph 700 showing the relative luminescence intensity at wavelengths longer than those associated with NV or NVN centers of a conventional luminescent nanodiamond powder 702 having an average diameter of 100 nm, measured between approximately 804 and 908 nm of light (along the x-axis), compared to that of a fully sintered carbonate PCD 104 and a fully sintered cobalt PCD 104, respectively, formed in the manner described above, where the carbonate PCD and the cobalt PCD are in the form of a fully sintered body. In this example, the cobalt PCD was formed from diamond grains having an average grain size of approximately 17 μm and subjected to a pressure of approximately 11 ksi (6.5-6.9 GPa) and a temperature of approximately 1450°C. The resulting cobalt PCD had a cobalt content of approximately 10 weight percent based on the total weight of the cobalt PCD. In this example, the carbonate PCD was formed from diamond grains having an average grain size of approximately 2 μm and subjected to a pressure of approximately 13.5 ksi (7.3-7.7 GPa) and a temperature of approximately 2200° C. The resulting carbonate PCD had a magnesium carbonate content of approximately 8 weight percent based on the total weight of the carbonate PCD. Emission at longer wavelengths is of interest in bioluminescence applications because it allows for the use of lower energy irradiation sources that are less damaging to photosensitive organic materials, living tissues, and the like. The data was collected by subjecting each diamond material to a laser operating at a wavelength of approximately 785 nm using a spectrometer Process Instruments model PI-100 and monitoring the emission from the diamond material. Graph 700 shows the average of 5-15 scans at random locations for each diamond material. As shown, the luminescence intensity measured at a wavelength of approximately 908 nm for the carbonate PCD 704 is approximately 30 percent higher than that of the conventional luminescent nanodiamond powder 702, demonstrating the increased level of luminescence intensity emitted by the luminescent diamond material in the form of carbonate PCD disclosed herein. The luminescence intensity measured at a wavelength of approximately 908 nm for the cobalt PCD 704 is approximately 8 percent higher than that of the conventional luminescent nanodiamond powder 702.The carbonate PCD used to generate the data in Figure 7 is in sintered form, i.e. in the form of a sintered body, which has not yet been size reduced to smaller or nano-sized particles or grains. As noted above, the process of grinding the sintered PCD body into smaller particle size, e.g. nano-sized diamond particles or grains, may subject the diamond material to further plastic deformation, which serves to enhance even further the luminescent activity / intensity of the resulting diamond particles.

[0021] Figure 8 is a graph 800 showing the relative luminescence intensity of various examples of luminescent diamond material in the form of cobalt PCD 802, 804 and 806, all within the optical wavelength range of about 810-915 nm (along the x-axis) as a function of various HPHT processing pressures, compared to a precursor diamond powder 810 that has not been subjected to the HPHT process. In each example, the cobalt PCD was formed from diamond grains or powder having an average grain size of about 17 μm using approximately 10 weight percent cobalt based on the total weight of the resulting cobalt PCD. The diamond powder 810 that has not been subjected to the HPHT process does not exhibit significant luminescence activity or intensity. Luminescent diamond in the form of sintered PCD formed using cobalt catalyst, i.e., cobalt PCD, exhibits increasing levels of luminescence intensity with progressively higher pressure processing conditions: 10.2 ksi and 1450°C for 802, 12.0 ksi and 1450°C for 804, and 13.5 ksi and 1450°C for 806, suggesting that increasing levels of plastic deformation in the diamond grains results in greater luminescence activity and higher luminescence intensity. The pressure levels of 10.2, 12.0, and 13.5 ksi correspond to the hydraulic pressures used to operate HPHT equipment. The conversion from hydraulic pressure to cell pressure is approximately as follows: 10.2 ksi = 6.0-6.4 GPa internal cell pressure, 12 ksi = 6.9-7.3 GPa internal cell pressure, and 13.5 GPa = 7.3-7.7 GPa internal cell pressure, with the ranges depending on both temperature and the specific cell design / materials used. This data shows that the luminescent diamond disclosed herein in the form of cobalt PCD exhibits at least two orders of magnitude, and in some cases at least three orders of magnitude, higher luminescence intensity than precursor diamond grains that have not been subjected to HPHT processing.As noted above for the data shown in Figure 7, the measured PCD sample is in the form of a fully sintered body that has not yet been crushed to the desired grain size, e.g., nano-sized diamond particles or grains.As described above, in some embodiments the process of reducing particle size 1) creates more diamond surface area for exposure to laser radiation under luminescent conditions and also 2) may subject the diamond material to even more plastic deformation, both of which mechanisms may act to further enhance the luminescent activity and luminescent intensity of the resulting diamond particle material.

[0022] In some embodiments, after subjecting the diamond precursor material to the HPHT solidification conditions / processing described above, the resulting diamond material is subjected to further treatment(s) for the purpose of further increasing the luminescence activity and intensity. For example, such additional treatment(s) may include subjecting the solidified diamond material to one or more further HPHT processes and / or exposing the solidified diamond material to other processing techniques / processes that subject the diamond grains to further plastic deformation. The further HPHT processing may be performed before or after size reduction. It should be understood that any such other techniques that act to subject the diamond material from the HPHT process to further plastic deformation that acts to increase the luminescence activity are within the spirit and scope of the present disclosure and may include, but are not limited to, mechanical collision of the diamond material with another object, substance or material that is expected to induce fracture and / or plastic deformation of the grains. The HPHT diamond material may be subjected to high temperatures to facilitate the migration of vacancies formed during HPHT to positions adjacent to the nitrogen impurities to form further nitrogen (NV and / or NVN) defects. In some embodiments the HPHT diamond material disclosed herein may be treated by ion bombardment and / or annealing or other conventional means useful for creating further NV and / or NVN defects, centres or sites in the diamond material. Such further treatment(s) may be carried out in a high temperature or ambient temperature environment. The use of charged nitrogen particles, for example contained within a nitrogen plasma chamber, may be used to create NV 0 (Uncharged Nitrogen Vacancy) Centers and NV -(negatively charged nitrogen vacancy) centers. The nature and extent of such treatment will be understood to vary depending on the specific diamond material and end use, and may include a single treatment, or a series / series of similar or different treatments. For example, NV centers have been found to be very useful as sensing devices for determining the strength of localized magnetic fields. In other examples, it may be useful to activate both NV and NVN centers, as well as additional luminescence centers active in the infrared region. The type of further treatment(s) used may also depend on whether the diamond material obtained from the HPHT process is in the form of sintered PCD, for example in the absence of catalytic material during the HPHT process, or in the form of semi-sintered and mechanically bonded diamond grains as described above. Such further treatment(s) is believed to enhance the luminescence intensity, either by creating more NV and / or NVN defects or centers, or by exposing more of these NV and / or NVN defects or centers by creating additional surface area during the crushing process.

[0023] In some embodiments where the luminescent diamond obtained from the HPHT process is in the form of a metal PCD, e.g., cobalt PCD, it may be desirable to process the sintered PCD body to completely or partially remove the metal material therefrom, which may be done by a leaching process or other processes known in the art to remove the metal catalyst from the PCD to enable its use in such applications where the presence of metal is undesirable or unacceptable, e.g., biological applications. Removing the catalyst material from the PCD also weakens the structure of the sintered body making it easier to crush and reduce in size. In some embodiments of the luminescent diamond described herein formed using a carbonate catalyst, e.g., carbonate PCD, such metal-free PCD does not contain metal and therefore may be used in biological end applications without the need for any catalyst removal. It may be useful to use magnetic separation to ensure that the luminescent diamond material is sufficiently free of the metal catalyst. Some embodiments of luminescent diamond provided in the form of carbonate PCD provide substantially higher luminescence intensity levels than cobalt PCD (as shown in FIG. 7), which may be due to the higher temperature and pressure levels used in the HPHT sintering process employed with carbonate PCD, as well as the higher relative transparency and lower opacity of carbonate PCD compared to cobalt PCD as noted above.

[0024] The luminescent diamonds disclosed herein may be resized after the HPHT solidification process to facilitate use in applications requiring smaller diamond particles, e.g., nano-sized particles, such as biological applications as discussed above. Thus, after solidifying the luminescent diamond by HPHT processing, it is subjected to a size reduction treatment for the purpose of breaking the diamond material into smaller diamond flakes or grains. In some embodiments, the luminescent diamond may be processed to reduce the size to an average diameter of about 1 nm to 1 mm, or about 5 nm to 200 μm, etc. Examples of useful average particle size ranges include, but are not limited to, 5 to 100 nm, 100 to 200 nm, 200 to 1000 nm, 0.500 to 20 μm, and 20 to 200 μm. In other examples, it may be useful to have an average particle size of 1 μm or more. The specific process used to reduce the size of the diamond material resulting from HPHT processing may and will likely vary depending on the specific material, for example, whether the diamond material is in the form of sintered PCD, partially sintered PCD, or mechanically bonded diamond grains. In some embodiments, the diamond material may be crushed by high-speed collision with a high-strength target, such as one made of tungsten carbide, or by collision with another diamond material, such as self-collision under high-speed conditions. In some embodiments, if the diamond material is to be used for biological applications, it is desirable to crush the diamond material into nano-sized pieces or particles. The process of crushing or resizing the diamond material may be carried out at high temperature or ambient temperature conditions, if such helps to make the process easier or if such causes the diamond material to undergo further plastic deformation to further increase the luminescence activity and luminescence intensity. Sorting by magnetic or other mechanical techniques may be used to separate luminescent diamond particles with cobalt inclusions from luminescent particles that do not contain cobalt inclusions.Some cellular structures are easily damaged by sharp edges such as those created by fragmented diamond crystals, so the shape of the resulting microparticles may be important depending on the end application. In these applications, it may be beneficial to employ detonation nanodiamonds as the starting material, since these microparticles are essentially spherical in shape. In some embodiments, treatment of the material in an oxidizing environment as described above, which has been shown to remove more than 50% of the diamond crystals under some conditions, can be employed to remove the sharp edges and increase the sphericity of the microparticles. In any of the powder sizing mentioned above, the proper definition of particle size is: This can be obtained by adopting the technique of equivalent circles with equal projected areas defined by the formula: TIFF0007669273000001.tif6146, where D EQPC is the diameter of a circle that has the same projected area A as the particle of interest.

[0025] As briefly mentioned above, during the process of grinding diamond material to a desired diamond grain size, e.g., nano-sized particles, the diamond material may undergo further plastic deformation or fracture, e.g., beyond that which occurred during the HPHT process, resulting in a higher luminescence activity and intensity of the resulting diamond material.Thus, the resulting resized diamond particles have a level of luminescence intensity greater than that of the diamond material after HPHT processing.Furthermore, if intermediate treatments as described above are performed between HPHT processing and resizing, the luminescence activity / intensity may increase twice between the later solidified diamond material during HPHT processing and the diamond particles after the grinding or resizing process.

[0026] FIG. 9 is a graph 900 showing the relative difference in luminescence intensity when comparing a luminescent diamond 902 as disclosed herein formed from carbonate PCD and sized to diamond particles (which may include some nano-sized particles) with both a conventional luminescent nanodiamond 904 and a cobalt PCD nanodiamond 906 (also sized to diamond particles). In this example, the cobalt PCD was formed from diamond grains having an average grain size of approximately 17 μm and subjected to a pressure of approximately 11 ksi (6.5-6.9 GPa) and a temperature of approximately 1450° C. The resulting cobalt PCD had a cobalt content of approximately 10 weight percent based on the total weight of the cobalt PCD. In this example, the carbonate PCD was formed from diamond grains having an average grain size of approximately 10 μm and subjected to a pressure of approximately 13.5 ksi (7.3-7.7 GPa) and a temperature of approximately 2200° C. The resulting carbonate PCD had a magnesium carbonate content of approximately 6 weight percent based on the total weight of the carbonate PCD.

[0027] FIG. 10 is a graph 1000 showing the difference in luminescence intensity of carbonate PCD in both sintered 1002 and crushed 1004, and cobalt PCD in both sintered 1006 and crushed 1008 states, relative to conventional luminescent nanodiamond (which is expressed as a relative luminescence intensity of 100 percent). In this example, the cobalt PCD was formed from diamond grains having an average grain size of approximately 17 μm and subjected to a pressure of approximately 11 ksi and a temperature of approximately 1450° C. The resulting cobalt PCD had a cobalt content of approximately 10 weight percent based on the total weight of the cobalt PCD. In this example, the carbonate PCD was formed from diamond grains having an average grain size of approximately 10 μm and subjected to a pressure of approximately 13.5 ksi (7.3-7.7 GPa) and a temperature of approximately 2200° C. The resulting carbonate PCD had a magnesium carbonate content of approximately 6 weight percent based on the total weight of the carbonate PCD. In one example, the luminescence intensity of crushed carbonate PCD diamond material may be increased by about 50 percent or more compared to sintered carbonate PCD diamond material, and the luminescence intensity of crushed cobalt PCD diamond may be increased by about 4 percent or more compared to sintered cobalt PCD diamond. With reference to Figure 10, the sintered carbonate PCD 1002 has a luminescence intensity about 30 percent higher than conventional luminescent nanodiamonds, the crushed carbonate PCD 1004 has a luminescence intensity about 100 percent higher than conventional luminescent diamonds, the sintered cobalt PCD 1006 has a luminescence intensity of about 7.9 percent of conventional luminescent diamonds, and the crushed cobalt PCD 1008 has a luminescence intensity of about 8.2 percent of conventional luminescent diamonds.

[0028] It should be understood that the exact amount of luminescence intensity increase may vary depending on factors such as the specific type of luminescent diamond material, the technique or process used for milling, and the final size of the luminescent diamond particles, other process treatments employed, such as heat treatment under vacuum conditions (as described above with respect to FIG. 5) and / or air heat treatment. In addition to exhibiting much higher luminescence intensity than conventional luminescent nanodiamonds, crushed carbonate luminescent diamonds maintained their luminescence intensity for a longer duration than conventional luminescent nanodiamonds when measured at 908 nm. For example, crushed carbonate luminescent diamonds were seen to reach a limiting luminescence intensity value close to about 0.97 for a 10-point scan, while conventional luminescent nanodiamonds were less than 0.93 for the same number of scans, yet the slope of the luminescence intensity declined rapidly.

[0029] In order to use the luminescent diamonds disclosed herein for certain downstream applications, such as biological applications, it may be desirable to further treat or functionalize the luminescent diamond particles, such as nanodiamonds, to make the material suitable for its intended application. It is understood that the method and type of treatment that may be used to functionalize the luminescent diamond materials disclosed herein will vary depending on the specific end use. However, one example of a functionalization process may involve oxygen termination along the diamond surface to make the diamond surface hydrophilic, which may be established by various surface oxidation procedures. Such oxygen termination functionalization may include forming a mixture of =O, -OH, -COOH, or -COC- groups on the surface. Other surface terminations may include hydrogen termination, halogenation, thermal annealing to create double bonds, and OH termination by reduction. A further type of functionalization may involve grafting or binding of specific molecules to the surface of the treated diamond, the treatment being carried out in a manner that has been shown to promote such binding, and such molecules are selected to react rapidly with various biomolecules. Further types of functionalization may include bio-labeling, which may occur by electrostatic (non-covalent) or covalent bonding of diamond particles with biomolecules.These are just a few examples of the way that the luminescent diamond disclosed herein can be functionalized for use in biological applications, and it should be understood that other known techniques and technologies useful for functionalizing luminescent diamond for specific biological applications are within the scope and spirit of this disclosure.

[0030] Although only a few example embodiments of luminescent diamond have been described in detail above, those skilled in the art will easily recognize that many modifications in the example embodiments are possible without substantially departing from the present invention.For example, the luminescent diamond disclosed herein has been presented in relation to biological end uses.It should be understood that the luminescent diamond disclosed herein may be used in end uses other than biological, where desired improved levels of luminescence intensity are useful or beneficial.Other potential applications of luminescent diamond include, but are not limited to, use in magnetic sensors, high-resolution thermography, fine sensor arrays, counterfeit prevention measures, iron concentration monitoring, membrane potential measurement, light capture, and strain / pressure sensors.Therefore, it is understood that it is not intended to limit the luminescent diamond disclosed herein to one particular end use.

[0031] Accordingly, all such modifications and end uses of the luminescent diamond are intended to be included within the scope of the present disclosure as defined in the following claims. In the claims, means-plus-function clauses are intended to encompass the structures described herein as performing the recited functions, and equivalent structures as well as structural equivalents. Thus, nails and screws may be equivalent structures in the context of fastening wooden parts, although nails may not be structural equivalents in that nails employ cylindrical surfaces to fasten wooden parts together, whereas screws employ helical surfaces. It is the express intention of the applicant not to invoke means-plus-function claims for any limitation of any claim herein, except where the claim expressly uses the term "means for" with the associated function.

Claims

1. A method for making a luminescent diamond, comprising: subjecting a quantity of precursor diamond grains to high pressure / high temperature conditions of 5.0 GPa to 10 GPa and at least 1300°C to plastically deform the precursor diamond grains and generate nitrogen vacancy defects in the precursor diamond grains. the resulting diamond grains exhibit a higher level of luminescence intensity than the precursor diamond grains; thereafter reducing the size of the diamond grains to form diamond grains having an average grain size of less than 20 μm. The method.

2. 10. The method of claim 1, wherein the quantity of precursor diamond grains subjected to the high pressure / high temperature conditions is substantially free of diamond sintering catalyst.

3. 2. The method of claim 1, further comprising heat treating the resulting diamond grains under vacuum conditions after said subjecting and prior to said reducing to further increase the level of said luminescence intensity.

4. The method of claim 1 , wherein after said reducing, said diamond grains have an average diameter of less than about 1000 nm in size.

5. The method of claim 1 , wherein a quantity of catalytic material is added to the quantity of precursor diamond grains prior to said subjecting.

6. 6. The method of claim 5, wherein after said subjecting and before said reducing, a quantity of said diamond grains are in a semi-sintered state.

7. 2. The method of claim 1 , wherein after said subjecting and before said reducing, the resulting diamond grains have an luminescence intensity level that is at least two orders of magnitude higher than an luminescence intensity of the precursor diamond grains.

8. 4. The method of claim 3, wherein after said heat treating and before said reducing, the resulting diamond grains have an luminescence intensity level that is at least three orders of magnitude higher than an luminescence intensity of the precursor diamond grains.

9. subjecting the precursor diamond grains to the high pressure / high temperature conditions in the presence of a catalytic material to form a polycrystalline diamond body; and 2. A method according to claim 1, comprising, prior to said reducing, heat treating the polycrystalline diamond body under vacuum conditions to achieve a level of luminescence intensity greater than that of the polycrystalline diamond body.

10. The method of claim 9, further comprising removing the catalytic material.

11. The method of claim 9, further comprising crushing the polycrystalline diamond body into diamond chips having an average diameter of about 10 to 1,000 nm.

12. 10. The method of claim 9, wherein a reduced amount of catalytic material is used during said subjecting, and the polycrystalline diamond body is semi-sintered.

13. 10. The method of claim 9, wherein after said subjecting and before said heat treating, the polycrystalline diamond body has an luminescence intensity at a level at least two orders of magnitude higher than an luminescence intensity of the quantity of precursor diamond grains.

14. 14. The method of claim 13, wherein after said heat treating, the polycrystalline diamond body has an luminescence intensity at a level 10 percent greater than the luminescence intensity of the polycrystalline diamond body before said heat treating.

15. the catalytic material is a carbonate catalytic material; and the polycrystalline diamond body has a level of luminescence intensity that is at least 10 percent higher than the polycrystalline diamond body prior to the heat treating step; 10. The method of claim 9.

16. 16. The method of claim 15, wherein after said heat treating, the polycrystalline diamond body has an emission intensity that is at least about two orders of magnitude higher than an emission intensity of the precursor diamond grains.

17. The method of claim 15, wherein said heat treating comprises crushing said polycrystalline diamond body into pieces having an average diameter of about 10 to 1,000 nm.

18. 16. The method of claim 15, wherein a reduced amount of the carbonate catalyst material is used during said subjecting, such that the polycrystalline diamond body is not fully sintered.

19. 16. The method of claim 15, further comprising functionalizing the heat treated polycrystalline diamond body piece after said heat treating.

Citation Information

Patent Citations

  • Discharge device

    JP2006172718A

  • Method for producing fine grain polycrystalline diamond compact

    JP2011225420A

  • Self-grown monopoly compact grit

    US20030044613A1

  • Chemical leaching / thermal decomposing carbonate in carbonate pcd

    US20150183091A1

  • Luminescent diamond material and method of producing the same

    WO2019209702A1